1994
DOI: 10.1002/anie.199409891
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Ring‐Opening Polymerization of Highly Strained, Ring‐Tilted [2]Ruthenocenophanes

Abstract: Only an ethylene bridge braces the Cp2Ru unit in the first [2]rutheno‐cenophane. This leads to a highly strained molecular framework (shown on the right) and makes [2]ruthenocenophanes suitable starting materials for thermal ring‐opening polymerization to give poly‐(ruthenocenylethylene)s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…The downfield shift of the signal assigned to the ipso carbon atom on the ruthenocene fragment of the zirconium-bridged [1]ruthenocenophane 69 is unusual for tilted ansa metallocenes, but consistent with the analogous [1]ferrocenophane (C ipso : d = 159.0 ppm). [28] Thermal ROP has been reported for ethane-bridged [2]ruthenocenophanes [153] and stanna [1]ruthenocenophanes [155] to yield high-molecular-weight polyruthenocenes.…”
Section: Metallocenophanes Of Rutheniummentioning
confidence: 97%
“…The downfield shift of the signal assigned to the ipso carbon atom on the ruthenocene fragment of the zirconium-bridged [1]ruthenocenophane 69 is unusual for tilted ansa metallocenes, but consistent with the analogous [1]ferrocenophane (C ipso : d = 159.0 ppm). [28] Thermal ROP has been reported for ethane-bridged [2]ruthenocenophanes [153] and stanna [1]ruthenocenophanes [155] to yield high-molecular-weight polyruthenocenes.…”
Section: Metallocenophanes Of Rutheniummentioning
confidence: 97%
“…Hydrogen atoms omitted for clarity. The a angle is 23.5(2) [12]. Figure used with permission from Ref.…”
Section: Ferrocenophanes Bridged With Transition Metalsmentioning
confidence: 99%
“…[155] The insoluble homopolymer had a conductivity of 10 À3 O À1 Á cm À1 , while the copolymer prepared with norbornene had M w and M n values of 21 000 and 11 000, respectively. Thermal ROP of [2] [157][158][159] Cyclic voltammetric studies of these polymers showed that the ruthenium-based polymers underwent irreversible oxidation, while the iron-based polymers underwent reversible oxidation. [158] Oxidation of the poly(ferrocenylethylene) with tetracyanoethylene (TCNE) resulted in antiferromagnetic interactions.…”
Section: Ring-opening Polymerizationmentioning
confidence: 99%
“…Thermal ROP of [2] [157][158][159] Cyclic voltammetric studies of these polymers showed that the ruthenium-based polymers underwent irreversible oxidation, while the iron-based polymers underwent reversible oxidation. [158] Oxidation of the poly(ferrocenylethylene) with tetracyanoethylene (TCNE) resulted in antiferromagnetic interactions. [159] Unsymmetrical [2]ferrocenophanes have also been synthesized and ring-opened by Manners and coworkers.…”
Section: Ring-opening Polymerizationmentioning
confidence: 99%